Structural Determination of Cephalexin/β-Cyclodextrin Inclusion Complex and its Validation using Molecular Simulation Methods - Sharma, Dinesh; Saraswat, Harish; Banoo, Syqa; Islam, Maidul (Asian Journal of Chemistry, 2020)
In this work, molecular simulation methods combining molecular docking and the structure elucidation of inclusion complex of cephalexin/β-cyclodextrin (β-CD) was determined using 1H NMR. Molecular docking studies showed that the complex formation process between β-CD and cephalexin was favourable and spontaneous because of negative values of binding energies. Molecular docking studies also confirmed the entry of aromatic ring into the cavity. Molecular mechanics studies were performed for aromatic ring of cephalexin, in different orientations and from both cavity ends, to measure the parameters of inclusion depth and mode of entry. The resultant structure was studied for HOMO-LUMO gap to validiate the method. The final structure was established using 1H NMR, molecular mechanics, HOMO-LUMO gap and molecular docking.